STUDY OF BIOCHEMICAL COMPOUNDS AND ANTIMICROBIAL ACTIVITY OF PLEUROTUS INDICA MUSHROOM - Pria, S; Shanmugapriya, O. N. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
In this study, the nutritional values of dietary mushrooms-Pleurotus indica that are very popular among the cultivated mushrooms in India have been determined. P.indica is widely cultivated as it is rich in nutrients and its component. P.indica is useful in biomass production in commercial level as it contains proteins and minerals. In this study the value added biochemical compounds in P.indica were analyzed from cultures. The amount of total carotenoids, protein, vitamin, pigments and phenolic compounds were examined. P.indica extracts possessed great potential antibacterial activities against four bacterial strains with inhibition zones ranged 8-15mm and MICs values ranges from 25-40É¥g/mL. Thus, it could be suggested that the P.indica is useful biosystem for production of biochemical compounds possess an antimicrobial principles.